Pengaruh Kepadatan Populasi Sitophilus oryzae (L.) terhadap Pertumbuhan Populasi dan Kerusakan Beras - Hendrival HENDRIVAL; Lilis MELINDA (Biospecies, 2017)
The research aims to study the effect population density of S. oryzae against population growth and damage of rice. The population density of S. oryzae is 5, 10, 15, and 20 pairs of adult per 250 g rice. The results showed that population density S. oryzae affects pest population growth of S. oryzae, characteristics loses weight of rice, percentage powder of rice, and changes content moisture of rice. The population density S. oryzae as many as 20 pairs of adult per 250 g of rice can increase populations pest S. oryzae, characteristics loses weight of rice, percentage powder of rice, and content moisture of rice. The relationship between population density S. oryzae with a growing population, percentage loses weight, percentage rice hollow, percentage powder of rice, and changes content moisture of rice increased linearly. There is a positive correlation between population density S. oryzae with population growth S. oryzae (r = 0.997**; P < 0.01), the percentage loses weight (r = 0.987*; P < 0.05), the percentage of rice perforated (r = 0.998**; P < 0.01), the percentage powder of rice (r = 0.997**; P < 0.01), and changes content moisture of rice (r = 0.964**; P < 0.01)Keywords: Sitophilus oryzae, population density, population growth, damage rice